2020
DOI: 10.1080/00083968.2019.1691028
|View full text |Cite
|
Sign up to set email alerts
|

Gendering women’s livelihoods in artisanal and small-scale mining: an introduction

Abstract: Until recently, women were largely invisible as miners within the array of initiatives, laws and policies seeking to regulate mining in sub-Saharan Africa. This invisibility is beginning to change as gender and women are increasingly referenced in mining reform initiatives. In this paper, we provide an overview of extant research on gender and women's livelihoods in artisanal and small-scale mining (ASM), mostly of precious or high-value minerals, and some of the gaps that the papers assembled in this special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In the last few years, one such policy and scholarly focus has been on women and (artisanal) mining. Combatting the still pervasive invisibilities of women in mining, there has been more policy and scholarly research as well as some civil society activism endeavouring to make visible the significant numbers of women involved in artisanal mining, which corresponds with a growing focus on ‘gender’ in policy and legal reforms across Africa and elsewhere (see Buss and Rutherford, forthcoming).…”
Section: On the Moral Politics Of Artisinal Mining Women And Labour:mentioning
confidence: 99%
“…In the last few years, one such policy and scholarly focus has been on women and (artisanal) mining. Combatting the still pervasive invisibilities of women in mining, there has been more policy and scholarly research as well as some civil society activism endeavouring to make visible the significant numbers of women involved in artisanal mining, which corresponds with a growing focus on ‘gender’ in policy and legal reforms across Africa and elsewhere (see Buss and Rutherford, forthcoming).…”
Section: On the Moral Politics Of Artisinal Mining Women And Labour:mentioning
confidence: 99%
“…Women play crucial roles in the ASM workforce (Armah et al., 2016; Buss & Rutherford, 2020; Danielsen & Hinton, 2020; Kumah et al., 2020; Orleans‐Boham et al., 2020). However, their contributions are largely classified and do not give a clear understanding of the important roles they play (Buss & Rutherford, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Women play crucial roles in the ASM workforce (Armah et al., 2016; Buss & Rutherford, 2020; Danielsen & Hinton, 2020; Kumah et al., 2020; Orleans‐Boham et al., 2020). However, their contributions are largely classified and do not give a clear understanding of the important roles they play (Buss & Rutherford, 2020). In the dominant literature, it has been reported that women in ASM engage in activities such as sorting stones, fetching water, sluicing, processing gold amalgam and transporting mine waste (Arthur‐Holmes, 2021; Buss et al., 2019, 2020; Hilson, Hilson, Siwale, & Maconachie, 2018; Rutherford & Buss, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies on people's livelihoods in Indonesia that examine the livelihood transformation stimulus carried out by the mining and tourism sectors. Several studies on the transformation of people's livelihoods are still partial, either due to the encouragement of the tourism sector (Chen, Xu, & Lew, 2020), the encouragement of the agricultural industry (Nguyen et al, 2019), the encouragement of the fisheries sector (Wanyonyi, Wamukota, Mwakha Alati, & Osuka, 2021), to the impetus of the mining sector (Buss & Rutherford, 2020). The development of only sustainable livelihood studies does not discuss based on the economic sector that is the stimulus for livelihood transformation and empirical findings in households and rural areas (Huang, Yang, Tuyến, Colmekcioglu, & Liu, 2022).…”
Section: Introductionmentioning
confidence: 99%